2019
DOI: 10.31234/osf.io/gu7xp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Five Factor Model of Perseverative Thought

Abstract: Background: Like diagnostic status, clinically-relevant thought remains overwhelmingly conceptualized in terms of discrete categories (e.g., worry; rumination; obsessions). However, definitions can vary widely. The area of perseverative thought (or clinically-relevant thought more broadly) would benefit substantially from a consensus-based, empirically-grounded taxonomy similar to the Hierarchical Taxonomy of Psychopathology (HiTOP; Kotov et al., 2017) or the “Big Five” for personality. This paper addresses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Sample 2. Participants were 286 adults ages 18 -74 (M age = 37.50, SD = 11.0; 52% cisgender women, 47% men, 0.4% transgender women; 84% White; 13% Black or African American; 5% Asian; 2% other; 10% Hispanic or Latino/a/x) recruited via Amazon Mechanical Turk (mTurk) as part of a larger study on perseverative thought (see Hallion et al, 2021 for additional study details). Participants were recruited in March and April 2018, which precedes a possible quality decline beginning in Summer 2018 (Chmielewski & Kucker, 2019).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample 2. Participants were 286 adults ages 18 -74 (M age = 37.50, SD = 11.0; 52% cisgender women, 47% men, 0.4% transgender women; 84% White; 13% Black or African American; 5% Asian; 2% other; 10% Hispanic or Latino/a/x) recruited via Amazon Mechanical Turk (mTurk) as part of a larger study on perseverative thought (see Hallion et al, 2021 for additional study details). Participants were recruited in March and April 2018, which precedes a possible quality decline beginning in Summer 2018 (Chmielewski & Kucker, 2019).…”
Section: Participantsmentioning
confidence: 99%
“…These include traditional categorical conceptualizations, which at a minimum include worry, which is described as future-focused and is often associated with anxious distress (Borkovec et al, 2004) and rumination, which can be past-or present-focused and which FACETS OF MINDFULNESS AND PT 6 typically involves negative self-appraisal, especially in the case of depressive rumination (also known as brooding; Nolen-Hoeksema, 1991;Nolen-Hoeksema et al, 2008). More recently, latent variable modeling studies have found support for a perseveration or cognitive dyscontrol dimension, which reflects a general tendency to experience thoughts that are repetitive, uncontrollable, or intrusive, irrespective of the content of those thoughts (e.g., Ehring et al, 2011;Harvey et al, 2004), with some studies also identifying other potential dimensions, such as valence (Hallion et al, 2021). Hybrid models have also been developed, offering evidence of shared general perseverative qualities, as well as unique features specific to different manifestations of perseverative thought (e.g., Hallion et al, 2021;McEvoy et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is now generally accepted that perseverative thought can be conceptualized in several ways. These include traditional categorical conceptualizations, such as worry (future-focused and associated with anxious arousal; Borkovec et al, 2004) and rumination (which tends to be pastor present-focused and involve negative self-appraisal; Nolen-Hoeksema, 1991); in terms of a single higher-order perseverative thought construct that reflects the tendency to experience thoughts characterized by repetitiveness, uncontrollability, or intrusiveness, irrespective of content (e.g., Ehring et al, 2011;Harvey et al, 2004); or in terms of dissociable dimensions of FACETS OF MINDFULNESS AND PT 5 uncontrollability, valence, and content (Hallion et al, 2019). Hybrid models have also been developed, offering evidence of a shared general perseverative quality and unique features specific to different manifestations of perseverative thought (e.g., McEvoy et al, 2010).…”
Section: Facets Of Mindfulness and Ptmentioning
confidence: 99%
“…Second, because verbal-linguistic activity interferes with worry (Leigh & Hirsch, 2011;Rapee, 1993), a verballinguistic control task was selected to promote neutrally-valenced cognition while minimizing worry spillover. Third, recent multilevel modeling studies from our group demonstrate a robust relationship between self-referential processing and subjective uncontrollability of thoughts, irrespective of thought valence (Hallion et al, 2019). These findings are consistent with a neurobiological model that we are exploring in current work, in which impaired decoupling of the frontoparietal cognitive control network and default mode network (the latter of which is heavily implicated in self-referential processing; Whitfield-Gabrieli & Ford, 2012) is a hypothesized neural mechanism by which perseverative thought persists (e.g., as in Christoff et al, 2009).…”
mentioning
confidence: 63%